Characterisation of the inner structure and surface of nanoporous sodium-borate-silicate glasses - Novikov, Alexander F. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
Results of investigations are reported which have been carried out with use of some physical and chemical techniques on the nanoporous sodium-borate-silicate glasses with pore sizes within 5–100 nm. Porous structure is formed due to the leaching-out of initial glass Na 7/23 with phase separation. Some important parameters of the vitreous framework have been determined: percentage distribution of pores sizes, fractal dimensionality of porous glass, crystallinity grade within vitreous bulk, phase composition of crystalline areas within silica framework. The survey of the measured spectral characteristics (mainly in the infrared wave range) of the porous glass surface and its interpretation are presented. Spectral behaviour of some species immobilised on the surface of nanopores is discussed. Interaction of the silica surface, adsorbates and ambient gas medium is interpreted on the basis of the Pearson–Lewis conception about hard and soft acids and bases.
Optica Applicata, Vol. 35, 2005, nr 4, s. 701-708
Keywords: optyka; anoporous glass; X-ray phase analysis of microcrystals; gas adsorption; surface adsorption sites; characteristic IR spectra of the glass surface